Feminization strategies in crustacean aquaculture - Harlioglu, Muzaffer Mustafa; Farhadi, Ardavan (Springer, 2017)
Crustacean aquaculture production has developed rapidly in recent years because there has been an increase in crustacean market demands in different regions of the world. The growth rate of the most cultured crustacean species depends on genders. Therefore, monosex crustacean aquaculture, all male or all female, is more suitable for achieving higher yields, with the ecological benefits of reducing the risk of cannibalism. In addition, feminization is also appropriate for increasing individual number in populations because males are able to copulate with more females. For this reason, sexual manipulations are important in crustacean reproduction units. This review focuses on the sex differentiation mechanism and the use of different strategies for feminization of economically important crustaceans. In this review, feminization strategies are divided into two main methods: direct feminization and indirect feminization (masculinization). Direct feminization includes (1) ablation of androgenic gland (AG), (2) silencing and suppression AG and androgenic gland hormones (AGHs), (3) hormone therapy (i.e., 17 beta-estradiol), and (4) polyploidy induction. This review also emphasizes how feminization is carried out for crustaceans belonging to the different sex determination systems (ZW or XY) by using indirect method. The intension of controlling sexual differentiation for crustaceans will continue to increase in the next a few years, either for basic research or for its utilization to crustacean aquaculture; hence, this review will be profitable for crustacean farmers and researches.
Keywords: Monosex; Production; Sex differentiation; Androgenic gland; Hormone